THE INFLUENCE OF TAX UNDERSTANDING, IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 23 OF 2018 AND TAX SOCIALIZATION ON MSME TAXPAYER COMPLIANCE AT KPP PRATAMA PANDEGLANG - Machfudoh; Andi; Soerono, Ayu Noorida (PT Larva Wijaya Penerbit, 2023)
This study aims to determine the effect of understanding taxation, implementing Government Regulation No. 23 of 2018 and understanding taxation on MSME taxpayer compliance (Micro, Small and Medium Enterprises) at the Pratama Pandeglang Tax Service Office. The population in this study are all MSME taxpayers in Pandeglang, and the sample used is 100 taxpayers. This research is quantitative. The type of data in this study is primary with data sources using questionnaires. Data analysis using Multiple Linear Regression analysis. The results of this study indicate that tax understanding and tax socialization have no effect on MSME taxpayer compliance, while the implementation of Government Regulation No. 23 of 2018 has a positive effect on MSME taxpayer compliance